Hydration and endocrine responses to intravenous fluid and oral glycerol - van Rosendal, S. P.; Strobel, N. A.; Osborne, M. A.; Fassett, R. G.; Coombes, J. S. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Athletes use intravenous (IV) saline in an attempt to maximize rehydration. The diuresis from IV rehydration may be circumvented through the concomitant use of oral glycerol. We examined the effects of rehydrating with differing regimes of oral and IV fluid, with or without oral glycerol, on hydration, urine, and endocrine indices. Nine endurance-trained men were dehydrated by 4% bodyweight, then rehydrated with 150% of the fluid lost via four protocols: (a) oral = oral fluid only; (b) oral glycerol = oral fluid with added glycerol (1.5 g/kg); (c) IV = 50% IV fluid, 50% oral fluid; and (d) IV with oral glycerol = 50% IV fluid, 50% oral fluid with added glycerol (1.5 g/kg), using a randomized, crossover design. They then completed a cycling performance test. Plasma volume restoration was highest in IV with oral glycerol > IV > oral glycerol > oral. Urine volume was reduced in both IV trials compared with oral. IV and IV with oral glycerol resulted in lower aldosterone levels during rehydration and performance, and lower cortisol levels during rehydration. IV with oral glycerol resulted in the greatest fluid retention. In summary, the IV conditions resulted in greater fluid retention compared with oral and lower levels of fluid regulatory and stress hormones compared with both oral conditions.